2021
DOI: 10.3390/nano11092448
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Assisted Synthesis of Luminescent Micro- and Nanocrystalline Eu-Based MOFs as Luminescent Probes for Heavy Metal Ions

Abstract: The luminescent coarse-, micro- and nanocrystalline europium(III) terephthalate tetrahydrate (Eu2bdc3‧4H2O) metal-organic frameworks were synthesized by the ultrasound-assisted wet-chemical method. Electron micrographs show that the europium(III) terephthalate microparticles are 7 μm long leaf-like plates. According to the dynamic light scattering technique, the average size of the Eu2bdc3‧4H2O nanoparticles is equal to about 8 ± 2 nm. Thereby, the reported Eu2bdc3‧4H2O nanoparticles are the smallest nanosized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 78 publications
1
3
0
Order By: Relevance
“…66,67 This indicated that both DMF and water molecules simultaneously work as reactants and solvents. The XRD patterns of the synthesized Eu-MOF (Eu 2 bdc 3 ·4H 2 O), which are highly consistent with the corresponding Eu-MOF crystal material in simulated XRD patterns Tb 2 bdc 3 ·4H 2 O and some of the Eu-MOF crystals reported in the literature, 68–70 are shown in Fig. 2B.…”
Section: Resultssupporting
confidence: 84%
“…66,67 This indicated that both DMF and water molecules simultaneously work as reactants and solvents. The XRD patterns of the synthesized Eu-MOF (Eu 2 bdc 3 ·4H 2 O), which are highly consistent with the corresponding Eu-MOF crystal material in simulated XRD patterns Tb 2 bdc 3 ·4H 2 O and some of the Eu-MOF crystals reported in the literature, 68–70 are shown in Fig. 2B.…”
Section: Resultssupporting
confidence: 84%
“…Figure I shows a consistent peak position and characteristic peaks of the Eu-TPA and Zn-TPA MOFs. It can be seen that the MOF exhibited the main diffraction peaks at 2 theta values of 14.74°, 15.59°, 21.81°, 24.59°, 28.49°, and 30.44° which are well consisted with the results in the literature that suggested a successful synthesis of the MOF by a one-step synthesis strategy confirming its crystalline nature. …”
Section: Characterization Of Uoz-5mentioning
confidence: 99%
“…For example, the electrochemical method can produce MOFs under mild reaction conditions. Ultrasonic-assisted and microwave-assisted methods [ 95 97 ] can produce uniformly seeded MOFs with better size control [ 98 , 99 ]. This is the case of a recent study for the preparation of Co-MOFs (TMU-51) by an ultrasound-assisted technique, in which, by tuning the power of ultrasound, smaller particles with controlled morphology were achieved, which finally resulted in an improved sensing performance for nitrophenol detection [ 100 ].…”
Section: Challenges and Perspectivesmentioning
confidence: 99%